Improving Students' Critical Thinking Skills in Mathematics Learning by Using Interactive Multimedia - Barizatul Islami; Murni Jafna (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the critical thinking skills of elementary school students in mathematics learning by using interactive multimedia. This study is a classroom action research with the Kemmis & Mc Taggart model with four steps in each cycle, namely planning, action, observation and reflection. The subjects of this study were fifth-grade students of MIN 44 Aceh Besar. The data of this study were collected using observation and test techniques. Observation was used to obtain data on teacher and student learning activities, while tests were used to measure students' critical thinking skills in mathematics learning. The collected data were then analyzed using descriptive statistical techniques. The results of the study indicate that interactive multimedia can improve students' critical thinking skills in mathematics learning in elementary schools. This is evident from the results of the analysis of the research data which showed that the percentage of student completeness experienced a significant increase in each cycle with details of pre-cycle 52.19%, then increased in cycle 1 to 76.74% and in cycle 2 to 89.13%. The average value achieved also increased with details of pre-cycle 76.19, cycle 1 obtained 85.33 and cycle 2 obtained 91.47. Furthermore, the results of the standard deviation test also showed that the standard deviation value decreased in each cycle, indicating that students' critical thinking skills were becoming more evenly distributed. Based on these results, interactive multimedia can be used as an alternative learning medium to address students' low critical thinking skills in elementary school mathematics.